Designing a Third Space Science Methods Course - Vick, Matthew (Innovations in Science Teacher Education, 2017)
The third space of teacher education (Zeichner, 2010) bridges the academic pedagogical knowledge of the university and the practical knowledge of the inservice K-12 teacher. A third space elementary science methods class was taught at a local elementary school with inservice teachers acting as mentors and allowing preservice teachers into their classes each week. Preservice teachers applied the pedagogical knowledge from the course in their elementary classrooms. The course has been revised constantly over six semesters to improve its logistics and the pre-service teacher experience. This article summarizes how the course has been developed and improved.